Antimicrobial Activity of Three Macrolepiota Species from Turkey - DULGER, BASARAN; HACIOGLU, NURCIHAN; AYDIN, GURHAN; UZUN, YUSUF (Asian Journal of Chemistry, 2010)
Three Macrolepiota species (M. heimii, M. rachodes and M. puellaris) were tested for their antimicrobial activity by using the disc diffusion method. The ethanol extract from the fruit bodies of mushrooms were assayed against 16 microorganisms. In comparison with the test antibiotics amikacin, chloramphenicol and nystatin, the ethanol extract obtained from M. heimii presented significant activity against Micrococcus species and Citrobacter freundii. The extracts have weak anti-yeast activity against the yeast cultures.